To solve the system of equations, we can use the method of elimination.
First, let's add the two equations together to eliminate the variable "x":
(7x + 3y) + (-7x + 9y) = (-25) + (-47)
Simplifying the left side and the right side separately:
7x - 7x + 3y + 9y = -25 - 47
12y = -72
Next, we can solve for the variable "y":
12y = -72
Divide both sides of the equation by 12:
y = -6
Now that we have the value of "y", we can substitute it back into one of the original equations to solve for "x". Let's use the first equation:
7x + 3y = -25
Substitute y = -6:
7x + 3(-6) = -25
Simplify:
7x - 18 = -25
Add 18 to both sides of the equation:
7x = -25 + 18
7x = -7
Divide both sides of the equation by 7:
x = -1
Therefore, the solution to the system of equations is x = -1 and y = -6.
Solve the system of equations.
7x+3y=−25
−7x+9y=−47
1 answer